Hyperhomocysteinemia exacerbates acute kidney injury via increased mitochondrial damage - Zhang, Mei; Dong, Rong; Da, Jingjing; Yuan, Jing; Zha, Yan; Long, Yanjun (Frontiers in Physiology, 2022)
Abstract: Acute kidney injury (AKI) is a complex and common set of multifactorial clinical syndromes, and associated with increased in-hospital mortality. There is increasing evidence that Hyperhomocysteinemia (HHcy) is highly associated with the development of a variety of kidney diseases, including acute kidney injury（AKI）. However, the pathogenesis of HHcy in AKI remains unclear. In this study, we investigated the effect and mechanism of HHcy on cisplatin-induced acute kidney injury in mice and NRK-52E cells cultured with HHcy. We confirmed that mice with HHcy had higher serum levels of creatinine and more severe renal tubule injury after cisplatin injection. We found that HHcy aggravated renal mitochondrial damage, mainly manifested as decreased ATP β, significantly increased cytoplasmic Cyt C expression, and a significantly decreased mitochondrial DNA (mtDNA) copy number. In addition, we found that HHcy accelerated cisplatin-induced renal DNA damage; culturing NRK-52E cells with homocysteine (Hcy) could significantly increase apoptosis and mitochondrial damage. Interestingly, we found that Mdivi-1 reduced Hcy -induced mitochondrial damage, thereby reducing the level of apoptosis. In conclusion, these results suggest that HHcy might aggravate the development of AKI by increasing mitochondrial damage, and that reducing Hcy levels or inhibiting mitochondrial damage may be a potential therapeutic strategy to delay the development of AKI.